A power system network splitting strategy based on contingency analysis - Saharuddin N.Z.; Abidin I.Z.; Mokhlis H.; Abdullah A.R.; Naidu K. (MDPI AG, 2023)
Computer programming; Electric load flow; Electric power transmission; Optimization; Outages; Cascading failures; Contingency analysis; Load shedding scheme; N-1 contingencies; Network splitting; Optimization techniques; Power system networks; Steady state stability; Electric load shedding